ISSUES OF HARMONIOUS DEVELOPMENT OF TECHNICAL AND ARTISTIC SKILLS IN SCULPTURE LESSONS - Qurbonova Sitora Yunus qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the importance of harmoniously developing both technical and artistic skills in sculpture lessons. The study explores pedagogical methods for integrating practical techniques with creative expression using traditional materials such as clay, gypsum, and wood, alongside modern materials like polymer and plastic. By balancing technical mastery and artistic imagination, students enhance their practical competence, creative thinking, and overall artistic development, ensuring comprehensive skill formation in sculpture education.